Pengaruh Word Of Mouth, Citra Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Omg Matte Kiss Lip Cream (Studi Kasus Mahasiswa FEB UNISMA Angkatan 2020) - Putri, Amalia Cahyani; Basalamah, Muhammad Ridwan; Normaladewi, Andi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to find out the impact of Word of Mouth, Brand Image, and Product Quality on Purchase Decision OMG Matte Kiss Lip Cream Case Study Students of the Faculty of Economics and Business of Islamic University of Armed Forces 2020. The method used in this study is a quantitative method using a Slovene formula of 87 respondents. The study used SPSS data analysis methods in analyzing of normality tests, classical assumption tests, hypothesis tests, double linear regression tests and adjusted R2 coefficient tests. The results showed that Word of Mouth does not significantly influence purchase decisions, Brand Image had significant influence on purchasing decisions, and Product Quality had significant impact on purchase decisions Keywords: Word of Mouth, Brand Image, Product Quality, Purchase Decision